Health Care Reform and Globalisation : The US, China and Europe in Comparative Perspective - Watson, Peggy (2012)
In the post-Cold War, post financial crisis era, health care is an issue of critical political, personal and economic concern. In the US, plans to address a troubled health care model were met by vocal opposition. In the UK and post-communist Europe, attempts to introduce aspects of that model have resulted in controversy and violent protests, while China and Russia have recently backpedalled on marketising reforms. This innovative book provides a timely analysis addressing the many dimensions of radical health care change.Bringing together three major geopolitical regions with strikingly different recent histories, this international cast of contributors, examines reform in US, China and Europe within a single study frame. They look at the processes that have been involved when countries with such diverse starting points try to move towards a globally shared health care framework. An underlying theme running through the chapters is access to care, and how it is shaped by moral economies, by what can be said and known, and by political and economic power. Health Care Reform and Globalisation confronts the interpretations and experiences of patients, professionals, and politicians of health care transformation in practice. It will be of interest to scholars from a range of diverse disciplinary backgrounds, including public health, anthropology, area studies, sociology, politics, social policy, geography and economics.